The First World War and its repercussions on Egypt between 1914-1918 - رجب, يوسف (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research deals with an important period in the history of Arab Egypt, which is the period of the First World War and its impact on the Arab region in general and Egypt in particular. Likewise, its importance increased after the opening of the Suez Canal. Britain subjected Egypt to direct military rule to prevent unrest in this vital region, and the Egyptian people who yearned for freedom and independence from colonial domination and restricting political freedoms were curbed This is to benefit in harnessing the Egyptian capabilities of agricultural crops and harnessing the people in potholes and building roads and bridges to facilitate the movement of the British army during the First World War, as Egypt lived in the four years of the war very bad conditions represented in extreme poverty and confiscations in addition to forced labor, but Egypt was unable to occupy the British For its lands and it was resisting until it gained its independence from the British occupation after massive sacrifices to reach the desired goal..